Membrane fusion and the transmembrane envelope glycoprotein of maedi visna virus - Cousens, Christina A.M. (The University of Edinburgh, 1994)
The transmembrane envelope glycoprotein, gp46 of maedi visna virus (MVV) was proposed to mediate membrane fusion between the virus and cell and between infected and uninfected cells on the basis of analogy with other viruses.

In order to look at the relationship between fusion and gp46, which is difficult to purify in quantity from virus preparations, recombinant gp46 (rgp46) was made. This first required cloning of the part of the MVV (strain EV1) env gene which encodes gp46. Sequence comparison with other viruses showed that gp46 is a typical transmembrane fusion protein, with a hydrophobic N-terminal fusion peptide. This putative fusion peptide was highly conserved between different MVV isolates although gp46 as a whole was only about 80% conserved.

rgp46 was expressed as fusion proteins in yeast and in bacteria, but could only be prepared at low yield and purity principally due to its toxicity to host cells. Immunised animals raised antibodies to rgp46 and sera from MVV-infected sheep specifically reacted with rgp46, whereas serum from uninfected sheep did not.

A fusion assay was developed using MVV to determine the effect of serum on MVV-mediated fusion. A significant difference was shown between the activity of sera from MVV-infected and uninfected sheep in the fusion assay: Serum from uninfected sheep generally enhanced fusion at low dilutions of serum (<1:64) and had no effect at higher dilutions, whereas serum from MVV infected animals tended to inhibit fusion at low serum dilutions (< 1:16) and enhance at higher dilutions

The effect of serum in the fusion assay was shown to be principally mediated by IgG and correlated with serum ELISA activity against a rgp46 preparation. This suggested a relationship between the presence of antibodies to gp46 and fusion modulatory activity.

These results may have important implications in consideration of potential vaccines and also in understanding how the virus can continue to replicate and eventually cause disease in the face of an apparently normal specific immune response.